NEW MOON DATES AND COORDINATES - Al Bermani, Mohammed; Al Baghdadi, Hayder (Iraqi Journal of Science, 2024)
Computer simulation have been developed to calculate the dates, ecliptical,equatorial and horizontal coordinates every month at al Najaf holy city. The newmoon starts at the moment when the ecliptic longitude of the sun matches that of themoon, i.e., the difference between them vanishes. The program can be used topredict the birth dates of the moon for the next ten year or more.